Pentecostal aesthetics : theological reflections in a pentecostal philosophy of art and aesthetics - Felix-Jager, Steven. (Global Pentecostal and Charismatic Studies, 2015)
Pentecostals have not sufficiently worked out a distinctively Pentecostal philosophy of art and aesthetics. In Pentecostal Aesthetics: Theological Reflections in a Pentecostal Philosophy of Art and Aesthetics , with a foreword by Amos Yong, Steven Félix-Jäger corrects this by reflecting theologically on art and aesthetics from a global Pentecostal perspective, particularly through a pneumatic Pentecostal lens. Félix-Jäger contends that a Pentecostal philosophy of art and aesthetics must comply with the global, experiential, and pneumatocentric nature of the Pentecostal movement. Such a philosophy can be ontologically grounded in a relativistic theory of art. Theological reflections concerning the nature and purpose of art must then be sensitive to the ontological foundations secured thereof. In this fashion, Pentecostals can gain ample insight about the Spirit's work in today's contemporary artworld.